Outbreak of invasive methicillin-resistant Staphylococcus aureus infection associated with acupuncture and joint injection - Murray, R.; Pearson, J.; Coombs, Geoffrey; Flexman, J.; Golledge, C.; Speers, D.; Dyer, J.; McLellan, D.; Reilly, M.; Bell, J.; Bowen, S.; Christiansen, K. (The University of Chicago Press, 2008)
OBJECTIVE. To describe an outbreak of invasive methicillin-resistant Staphylococcus aureus (MRSA) infection after percutaneous needle procedures (acupuncture and joint injection) performed by a single medical practitioner. SETTING. A medical practitioner's office and 4 hospitals in Perth, Western Australia. PATIENTS. Eight individuals who developed invasive MRSA infection after acupuncture or joint injection performed by the medical practitioner. METHODS. Weperformed a prospective and retrospective outbreak investigation, including MRSA colonization surveillance, environmental sampling for MRSA, and detailed molecular typing of MRSA isolates. We performed an infection control audit of the medical practitioner's premises and practices and administered MRSA decolonization therapy to the medical practitioner. RESULTS. Eight cases of invasive MRSA infection were identified. Seven cases occurred as a cluster in May 2004; another case (identified retrospectively) occurred approximately 15 months earlier in February 2003. The primary sites of infection were the neck, shoulder, lower back, and hip: 5 patients had septic arthritis and bursitis, and 3 had pyomyositis; 3 patients had bacteremia, including 1 patient with possible endocarditis. The medical practitioner was found to be colonized with the same MRSA clone [ST22-MRSA-IV (EMRSA-15)] at 2 time points: shortly after the first case of infection in March 2003 and again in May 2004. After the medical practitioner's premises and practices were audited and he himself received MRSA decolonization therapy, no further cases were identified. CONCLUSIONS. This outbreak most likely resulted from a breakdown in sterile technique during percutaneous needle procedures, resulting in the transmission of MRSA from the medical practitioner to the patients. This report demonstrates the importance of surveillance and molecular typing in the identification and control of outbreaks of MRSA infection. © 2008 by The Society for Healthcare Epidemiology of America. All rights reserved.